Digital Capabilities, Integration into Global Innovation Networks, and Enterprise Innovation Performance - Shanwu Tian; Xiaozhen Lai; Lijun Dong; Xiurui Xu (Systems)
Against the backdrop of accelerated global digital transformation and the shift toward open innovation models, this study examines how enterprises leverage digital capabilities to integrate into global innovation networks (GINs) and enhance innovation performance, while exploring the moderating role of organizational flexibility. Drawing on dynamic capability and social network theories, a multidimensional framework of digital capabilities (perception, operation, and coordination) and organizational flexibility (cultural, resource, and capability) is proposed. The empirical analysis of 343 Chinese multinational corporations using SPSS 27 and AMOS 24 reveals three key findings: (1) all dimensions of digital capabilities significantly improve innovation performance; (2) GIN integration partially mediates this relationship by facilitating resource acquisition and collaboration; and (3) capability flexibility positively moderates the GIN–performance link, while cultural and resource flexibility show no significant effects. This study advances digital capability research by emphasizing dynamic processes over static technology adoption and provides practical insights for balancing technological investments with organizational adaptability.